2022
DOI: 10.3390/app12031621
|View full text |Cite
|
Sign up to set email alerts
|

A New Era for the Early and Non-Invasive Diagnosis of Giant Cell Arteritis: The Use of Fast-Track Ultrasound in Clinical Practice

Abstract: Background: The assessment of giant cell arteritis (GCA) in fast-track assessment clinics (FTA) including the use of ultrasound (US) is becoming the preferred practice in specialized centers. Methods: Patients with suspected GCA referred to the FTA of the Rheumatology Department, University of Pavia, Italy, between 2016 and 2021 were included to analyze the clinical and US findings. Results: A total of 553 US examinations were performed on 347 patients. A total of 246 were female (71%), and the mean age was 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A proposed method of optimising early diagnostic accuracy and, indeed, overall patient outcomes is the implementation of fast-track clinics [35] . The use of such fast-track clinics in GCA has been widely reported, with benefits including rapid and accurate diagnosis, reduced risk of permanent visual impairment, in addition to overall increased cost-effectiveness vs. standard care [35][36][37][38][39] . To date, only two studies have reported on the use of fast-track clinics in PMR, with both demonstrating that providing timely and easily accessible specialist care improves diagnosis and, indeed, patient outcomes [40,41] .…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…A proposed method of optimising early diagnostic accuracy and, indeed, overall patient outcomes is the implementation of fast-track clinics [35] . The use of such fast-track clinics in GCA has been widely reported, with benefits including rapid and accurate diagnosis, reduced risk of permanent visual impairment, in addition to overall increased cost-effectiveness vs. standard care [35][36][37][38][39] . To date, only two studies have reported on the use of fast-track clinics in PMR, with both demonstrating that providing timely and easily accessible specialist care improves diagnosis and, indeed, patient outcomes [40,41] .…”
Section: Clinical Diagnosismentioning
confidence: 99%